Electrodeposition of (111)-oriented and nanotwin-doped nanocrystalline Cu with ultrahigh strength for 3D IC application. (11th March 2021) - Zheng, Zeyang; Huang, Yu-Ting; Wang, Zhenyu; Zhang, Mingyang; Wang, Wei-Ting; Chung, Chih-Chun; Cherng, Sheng-Jye; Tsai, Ya-Hui; Li, Po-Chien; Lu, Zhouguang; Chen, Chih-Ming; Feng, Shien-Ping
Abstract: The mechanical performance of electroplated Cu plays a crucial role in next-generation Cu-to-Cu direct bonding for the three-dimension integrated circuit (3D IC). This work reports direct-current electroplated (111)-preferred and nanotwin-doped nanocrystalline Cu, of which strength is at the forefront performance compared with all reported electroplated Cu materials. Tension and compression tests are performed to present the ultrahigh ultimate strength of 977 MPa and 1158 MPa, respectively. The microstructure of nanoscale Cu grains with an average grain size around 61 nm greatly contributes to the ultrahigh strength as described by the grain refinement effect. A gap between the obtained yield strength and the Hall–Petch relationship indicates the presence of extra strengthening mechanisms. X-ray diffraction and transmission electron microscopy analysis identify the highly (111) oriented texture and sporadic twins with optimum thicknesses, which can effectively impede intragranular dislocation movements, thus further advance the strength. Via filling capability and high throughput are also demonstrated in the patterned wafer plating. The combination of ultrahigh tensile/compressive strength, (111) preferred texture, superfilling capability and high throughput satisfies the critical requirement of Cu interconnects plating technology towards the industrial manufacturing in advanced 3D IC packaging application.